THE INFLUENCE OF THE BIG FIVE PERSONALITY FACTORS IN KNOWLEDGE SHARING - Edi, Edi (Jurnal Manajemen Akuntansi Dan Administrasi Bisnis, 2020)
Knowledge is a combination of various elements such as experience, expert view that can be used as a basis to understand new experience or information. Knowledge will grow if it is shared. Knowledge sharing (KS) can happen is depend on enablers. One of them is high levels of trust. Research showed that there is a relationship between personality and interpersonal trust. The Big Five Personality (BFP) factors have been used to observe different personality traits. Those factors are Extraversion, Neuroticism, Openness to Experience, Agreeableness, and Conscientiousness. In this research project, the researcher wants to prove whether there is a relationship between the BFP factors and KS. Data were collected from undergraduate students from Faculty of Creative Multimedia (FCM) and Faculty of Management (FOM) in Multimedia University (MMU) to support the research. Based on the sample, this study determines which factors of the BFP that have potential to influence KS. This study cannot represent the generalisation of undergraduate students in Malaysian universities because of the small sample and the author only focused on one university. Recommendations have been given for other researchers who have desire to pursue their research in this topic. Kata Kunci : knowledge sharing, big five personality